FAKTOR YANG MEMPENGARUHI FREKUENSI REGURGITASI PADA BAYI 0 - 6 BULAN FACTORS AFFECTING REGURGITATION FREQUENCY IN INFANTS 0 - 6 MONTHS - Hasrida; Jusmawati; Yoan Titi Colauw (Stikes Graha Edukasi Makassar, 2023)
Background: Regurgitation is an event that is often experienced by babies, namely the release of a small portion of stomach contents some time after eating. Purpose: The purpose of this study was to determine the effect of breastfeeding techniques on the frequency of regurgitation in infants 0-6 months in the working area of ??the Kapasa Health Center, Makassar. Design: This type of research uses the pre-experimental method (one group pre-test and post-test design). The population in the study were all mothers who had babies who experienced regurgitation in the working area of ??the Kapasa Makassar Public Health Center, totaling 22 people. Results: The results of the study used the Wilcoxon Statistical test, which found a value of p = 0.001 <0.05. Conclusion: The conclusion in this study is that there is an effect of breastfeeding techniques on the frequency of regurgitation in infants 0-6 months. Suggestion: Therefore it is hoped that health workers can provide information and education to mothers about the importance of practicing good and correct breastfeeding techniques so as to reduce the occurrence of regurgitation in babies